Structure and dipole moment of catechol in hydroxylic solvents - Rudyk, Roxana Amelia (2004)
Motivation. Various classes of flavonoids of great importance for medicine have a molecular structure containing a resorcinol in its A-ring whereas the B-ring is a catechol derivative. With a future view to establishing correlations between the physicochemical and biological properties of flavonoids and catechols and with the specific aim of explaining the dipole moment of catechol in water, we investigated the molecular conformations and solute-solvent interactions of catechol in ethanol, methanol and water. Method. Basis sets at two levels of theory: HF/6-31G(d,p) and B3LYP/6-31G(d,p) were used for calculations. Onsager's method was used to analyze the solvent effects on the conformers of catechol. Results. A conformational equilibrium between the two main conformers of non-solvated catechol was proposed. The total energies, dipole moments, structural molecular and reactivity parameters of the conformers and transition states involved were calculated. These theoretical magnitudes were correlated with properties of the solvating solvents. The properties of solute-solvent association complexes formed by a molecule of catechol and three molecules of water by means of intermolecular hydrogen bonds were also calculated. Conclusions. The stability of the conformer that has one intramolecular hydrogen bond increases with the hydrogen-bond donor capability and polarity of the solvents. The dipole moment of catechol in water (11.45 D) is due to the solute-solvent association complexes, which are the predominant forms of the compound in aqueous solutions.